Q
S (
![ln(?) (\sqrt{x} - 1 \div \sqrt{x}) ^{2} dx ln(?) (\sqrt{x} - 1 \div \sqrt{x}) ^{2} dx](https://tex.z-dn.net/?f=++ln%28%3F%29++%28%5Csqrt%7Bx%7D++-+1+%5Cdiv++%5Csqrt%7Bx%7D%29+%5E%7B2%7D+dx)
Attachments:
![](https://hi-static.z-dn.net/files/d45/140421203a74e592d97d7bc93e76e005.jpg)
Answers
Answered by
0
Answer:
By parts.
Explanation:
You can integrate it by parts with the rule
∫
f
'
(
x
)
g
(
x
)
d
x
=
f
(
x
)
g
(
x
)
−
∫
f
(
x
)
g
'
(
x
)
where we assume that
f
'
(
x
)
=
1
and
g
(
x
)
=
ln
(
x
+
√
x
2
+
1
)
consequently
f
(
x
)
=
x
and
g
'
(
x
)
=
1
√
x
2
+
1
.
The integral is then
∫
ln
(
x
+
√
x
2
+
1
)
d
x
=
x
ln
(
x
+
√
x
2
+
1
)
−
∫
x
√
x
2
+
1
d
x
=
x
ln
(
x
+
√
x
2
+
1
)
−
√
x
2
+
1
+
C
.
Step-by-step explanation:
mark me brainliest please
Similar questions